The Comprehensive Literature Review of Surgical Management of Omphalocele - Yosie Yulanda Putra; Ririn Azhari (The Indonesian Journal of General Medicine, 2024)
Background: The surgical management of omphalocele has undergone significant evolution over the past decade, with various studies contributing to a deeper understanding of treatment modalities and outcomes.  Literature Review: In developing countries, challenges persist, particularly in managing ruptured omphaloceles where resources are limited. The adaptation of surgical techniques, such as employing simple suture methods in the absence of advanced materials, underscores the need for flexibility in surgical management (Komlatsè Akakpo-Numado et al., 2012). Furthermore, innovative conservative management approaches have shown promise, with gentian violet yielding satisfactory survival rates and reduced hospital stays, emphasizing the role of a multidisciplinary team in optimizing care (Rahman Mitul & Ferdous, 2012). The importance of individualized treatment plans is reinforced by findings from a tertiary care center, which advocate for conservative approaches in cases of giant omphalocele, utilizing staged management strategies that prioritize patient safety . Moreover, systemic inflammation's role in pulmonary hypertension related to isolated giant omphalocele further emphasizes the need for prenatal diagnosis and careful postnatal management, suggesting that a "paint-and-wait" approach can be beneficial (Teillet et al., 2022). Conclusion: In conclusion, the surgical management of omphalocele encompasses a variety of strategies that reflect the complexity of the condition and the necessity for individualized care. The literature collectively emphasizes the importance of adapting surgical techniques to specific patient needs, the benefits of conservative management in certain contexts, and the critical role of multidisciplinary teams in improving patient outcomes.